2019
DOI: 10.4314/ahs.v19i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of cardiovascular risk assessment among rural community dwellers in ezionum, Nigeria-implications for public health

Abstract: BackgroundCardiovascular disease is a major cause of mortality worldwide. Risk assessment has been shown to reduce cardiovascular morbidity and mortality. In view of their proximity and accessibility, community pharmacies could be a suitable site for cardiovascular risk assessment and other preventive health activities especially in rural underserved populations. The objective of this study was to assess outcome of cardiovascular risk assessment among rural community dwellers.Materials and methodsFive hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…There were fifteen studies identified across six countries that explored the service provision of pharmacy professionals in the prevention and control of NCDs [ 18 , 19 , 20 , 21 , 28 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Diabetes, hypertension, obesity, weight management, dyslipidemia, physical inactivity, an unhealthy diet, smoking, and alcohol misuse were among the health conditions primarily targeted by the interventions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were fifteen studies identified across six countries that explored the service provision of pharmacy professionals in the prevention and control of NCDs [ 18 , 19 , 20 , 21 , 28 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Diabetes, hypertension, obesity, weight management, dyslipidemia, physical inactivity, an unhealthy diet, smoking, and alcohol misuse were among the health conditions primarily targeted by the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The level C evidence centered on the pharmacy professional-led screening and management of infections and NCDs [ 20 , 25 , 28 , 45 , 51 , 54 , 55 ], antimicrobial stewardship programs [ 62 , 63 , 64 , 65 ], and emergency contraception supply [ 23 ]. The majority of the studies generating level D evidence utilized surveys, with or without mystery patient methodology, to examine the actual practice of pharmacy service provision, while a few used qualitative interviews or focus group discussions with mystery patient methodology [ 18 , 19 , 21 , 22 , 24 , 26 , 27 , 43 , 44 , 46 , 47 , 48 , 49 , 50 , 53 , 56 , 57 , 59 , 60 , 61 , 66 , 67 , 68 , 69 , 70 ]. One-quarter of the included studies ( n = 9) examined processes such as acceptability and feasibility of specific services [ 20 , 25 , 44 , 45 , 47 , 54 , 59 , 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We begin with three interesting papers on the cardiovascular system. Adje and others1, have written a research paper on cardiovascular risk assessment from a community in Nigeria.…”
Section: Now To Ncdsmentioning
confidence: 99%